Orally Administered Fumonisins Affect Porcine Red Cell Membrane Sodium Pump Activity and Lipid Profile without Apparent Oxidative Damage - András Szabó; Omeralfaroug Ali; Katalin Lóki; Krisztián Balogh; Miklós Mézes; Tibor Bartók; Levente Horváth; Melinda Kovács (Toxins, 2020)
Weaned piglets (n = 3 × 6) were fed 0, 15 and 30 mg/kg diet fumonisin (FB1, FB2 and FB3, i.e., FBs, a sphinganine analogue mycotoxin), from the age of 35 days for 21 days, to assess mycotoxin induced, dose-dependent changes in the red cells’ membrane. Ouabain sensitive Na+/K+ ATPase activity was determined from lysed red cell membranes, membrane fatty acid (FA) profile was analysed, as well as antioxidant and lipid peroxidation endpoints. Final body weight was higher in the 30 mg/kg group (vs. control), even besides identical cumulative feed intake. After 3 weeks, there was a difference between control and the 30 mg/kg group in red cell membrane sodium pump activity; this change was dose-dependent (sig.: 0.036; R2 = 0.58). Membrane FA profile was strongly saturated with non-systematic inter-group differences; pooled data provided negative correlation with sodium pump activity (all individual membrane n6 FAs). Intracellular antioxidants (reduced glutathione and glutathione peroxidase) and lipid peroxidation indicators (conj. dienes, trienes and malondialdehyde) were non-responsive. We suppose a ceramide synthesis inhibitor (FB1) effect exerted onto the cell membrane, proven to be toxin dose-dependent and increasing sodium pump activity, with only indirect FA compositional correlations and lack of lipid peroxidation.